استخدام بعض مهارات الوظائف التنفيذية في تنمية التواصل الاجتماعي لخفض الاضطرابات السلوكية للتلاميذ ذوي صعوبات التعلم - أبو زيد، لبنى شعبان أحمد (جامعة الإسكندرية - كلية رياض الأطفال, 2018)
هدف البحث الحالي إلى استخدام بعض مهارات الوظائف التنفيذية في تنمية التواصل الاجتماعي لخفض الاضطرابات السلوكية للتلاميذ ذوي صعوبات التعلم، واستخدمت الباحثة المنهج التجريبي بطريقة المجموعتين التجريبية والضابطة للتحقق التجريبي من استخدام بعض مهارات الوظائف التنفيذية كمتغير مستقل لتنمية التواصل الاجتماعي وخفض الاضطرابات السلوكية كمتغير تابع، وتكونت عينة البحث من مجموعتين إحداهما تجريبية والأخرى ضابطة، قوام كل منهما (20) تلميذا من التلاميذ ذوي صعوبات التعلم من الصفوف الثلاثة الأولى الذين تراوحت أعمارهم بين (84-108) شهرا، وقامت الباحثة بتطبيق أدوات الدراسة على العينة والتي تمثلت في 1- مقياس المسح النيورولوجي، إعداد عبد الوهاب كامل. 2- مقياس ستانفورد بينيه للذكاء- الصورة الخامسة. 3- مقياس صعوبات التعلم في القراءة إعداد فتحي الزيات. 4- مقياس التواصل الاجتماعي (إعداد الباحثة). 5- مقياس الاضطرابات السلوكية (إعداد الباحثة). 6- البرنامج القائم على مهارات الوظائف التنفيذية (إعداد الباحثة). وتوصلت نتائج الدراسة إلى 1- توجد فروق ذات دلالة إحصائية بين متوسطات رتب درجات أفراد المجموعة التجريبية على مقياس التواصل الاجتماعي في القياسين القبلي والبعدي بعد تطبيق البرنامج القائم على الوظائف التنفيذية في اتجاه القياس البعدي". 2- "توجد فروق ذات دلالة إحصائية بين متوسطات رتب درجات أفراد المجموعتين التجريبية والضابطة على أبعاد مقياس التواصل الاجتماعي في القياس البعدي لصالح المجموعة التجريبية". 3- لا توجد فروق ذات دلالة إحصائية بين متوسطات رتب درجات أفراد المجموعة التجريبية على أبعاد التواصل الاجتماعي في القياسين البعدي والتتبعي بعد مرور فترة المتابعة ومدتها شهر من انتهاء تطبيق البرنامج القائم على الوظائف التنفيذية. 4- توجد فروق ذات دلالة إحصائية بين متوسطات رتب درجات أفراد المجموعة التجريبية على مقياس الاضطرابات السلوكية في القياسين القبلي والبعدي بعد تطبيق البرنامج القائم على الوظائف التنفيذية في اتجاه القياس البعدي" 5- توجد فروق ذات دلالة إحصائية بين متوسطات رتب درجات أفراد المجموعتين التجريبية والضابطة على مقياس الاضطرابات السلوكية في القياس البعدي لصالح المجموعة التجريبية". 6- لا توجد فروق ذات دلالة إحصائية بين متوسطات رتب درجات أفراد المجموعة التجريبية على مقياس الاضطرابات السلوكية في القياسين البعدي والتتبعي بعد مرور فترة المتابعة ومدتها شهر من انتهاء تطبيق البرنامج القائم على الوظائف التنفيذية.
The current research aims to use some executive functions skills in developing social communication to reduce behavioral disorders in pupils with learning disabilities. The researcher used the experimental approach with two groups: experimental and control groups to verify the experimental use of some executive functions skills as an independent variable to develop social communication and reduce behavioral disorders as a dependent variable. The research sample consisted of two groups, one is experimental and the other is a control. Each group consisted of (20) pupils with learning disabilities attending the first three primary stage grades. Their ages ranged between (84-108) months. The researcher applied the study tools to the sample, which were: The neurological survey scale (prepared by Abdel-Wahab Kamel), Stanford Binet Intelligence Scale- Fifth Image, Reading learning disabilities scale (prepared by Fathy El Zayat), Social communication scale (prepared by the researcher), Behavioral disorders scale (prepared by the researcher), and a program based on executive functions skills (prepared by the researcher). The results indicated that there are statistically significant differences between the mean scores of the members of the experimental group on the social communication scale in the pre and post measures after program application based on executive functions in favor of post measure. There are statistically significant differences between the mean ranks of members in experimental and control group on the dimensions of Social communication scale in the post measure in favor of experimental group. There are no statistically significant differences between the mean ranks of members in experimental group on the dimensions of Social communication scale in the post and follow up measure after one-month follow up period after the end of program based on executive functions. There are statistically significant differences between the mean ranks of members in experimental and control group on the dimensions of behavioral disorders scale in the pre and post measures after program application based on executive functions in favor of post measure. There are statistically significant differences between the mean ranks of members in experimental and control group on behavioral disorders scale in the post measure in favor of experimental group. There are no statistically significant differences between the mean ranks of members in experimental group on behavioral disorders scale in the post and follow up measure after one month follow up period after the end of program based on executive functions.
Keywords: علم النفس التربوي -- التربية الخاصة -- صعوبات التعلم -- التواصل الاجتماعي -- الاضطرابات السلوكية